Pengaruh Pemberian Baluran Bawang Merah (Allium ascalonicum) terhadap Perubahan Demam pada Balita Pasca Imunisasi DPT Pentabio di PMB Yunia Lucky Afifah, A.Md.Keb Kecamatan Jabung Kabupaten Malang - Jannah, Miftahul; Safitri , Rani; Purwati, Anik (Jurnal Nusantara Mandani, 2024)
This study aims to evaluate the effect of red onion dressing on changes in fever in toddlers after DPT Pentabio immunization at PMB Yunia Lucky Afifah, Jabung District, Malang Regency. A quasi-experimental method with a post-test only control group design was used in this research. The research sample consisted of 34 toddlers who met the inclusion and exclusion criteria. Body temperature data was measured at two time intervals, namely 15 and 30 minutes after treatment. The results of the analysis showed that red onion smear therapy was significant in reducing the body temperature of toddlers, especially at a time interval of 30 minutes after treatment. The conclusion of this research is that red onion rub therapy is effective in reducing fever in toddlers after Pentabio DPT immunization, with important implications in the health management of toddlers. Keywords: Red onion rub, fever, immunization, DPT Pentabio, toddlers, traditional medicine